SECRETS OF QUR'AN INTERACTION AND BRAIN HEALTH - Arifin, Hasanul; Septadina, Indri Seta (International Islamic Medicine Forum, 2022)
Human beings were created by Allah with complex and complex structures and functions. The more we try to dig about the brain, it will never end. Therefore, everything that Allah made every part of us is a sign of Allah's greatness that should be our contemplation together. There is a term that states that understanding how the brain works is the main way to uncover the very essence of human beings. Character (morals or behavior) is the most important thing that must be owned by every human being and we must observe and analyze that the brain is the center of human character. The brain is part of the composition of the central nervous system that works as a center for controlling human activities in the form of thinking, moving, behaving, feeling something, remembering, and so on. Without the brain, humans will not live, like inanimate objects, without any use and potential. If we talk about interactions with the Qur'an that humans do such as reading, memorizing, listening, meditating or contemplating the meaning of the Qur'an, then this will affect the function directly or indirectly even the structure and function of the brain itself microscopically cellular can be affected. Many studies have been conducted to prove how the effects of the Qur'an from listening, reading, memorizing the Qur'an to brain function, especially in terms of brain waves, mental health, and so on. Health effects can be obtained very much before we interact with the Qur'an. If we analyze simply the stages of a person's activity before interacting with the Qur'an also indirectly has a positive impact on the body.